The Role of Trust and Migrant Investments in DiasporaHomeland Development Relations - Kandilige, Leander (African Human Mobility Review, 2021)
Research into the role of diaspora communities in origin countries’ development is a growing phenomenon. However, there is little understanding of the role of trust in mediating transnational relationships between migrants and recipients of remittances (non-migrants, members of migrant households and community leaders). Using a case study methodology, mixed methods and a comparative approach – in-depth interviews with 40 key informants (20 in the UK and 20 in Ghana), 120 questionnaires administered in the UK and 346 questionnaires administered in Ghana – this paper examines differing conceptualisations of trust among ‘development partners’ in the process of negotiating as well as implementing migrant-funded development projects. It also examines the nature of investments of migrants in the origin country. Migrant respondents are from the Kwahuman Traditional Area and the Upper East Region of Ghana. Ghana is used as a case study to examine this phenomenon both from the perspective of the migrant and that of the origin country partners. Narratives by migrants are examined in order to unearth factors that inform their decision-making and the approaches they adopt to ensure accountability.